Subcellular localization of a variable surface glycoprotein phosphatidylinositol-specific phospholipase-C in African trypanosomes (The Rockefeller University Press, 1987)
African trypanosomes contain a membrane-bound enzyme capable of removing dimyristylglycerol from the membrane-attached form of the variable surface glycoprotein (mfVSG; Ferguson, M. A. J., K. Halder, and G. A. M. Cross, 1985, J. Biol Chem., 260:4963-4968). Although mfVSG phospholipase-C has been implicated in the removal of the VSG from the trypanosome surface (Cardoso de Almeida, M. L., and M. J. Turner, 1983, Nature (Lond.)., 302:349-352; Ferguson, M. A. J., K. Halder, and G. A. M. Cross, 1985, J. Biol Chem., 260:4963-4968), its precise function and subcellular location have not been determined. We have developed a procedure for the separation of the cell fractions and organelles of Trypanosoma brucei brucei (and other trypanosome species) by differential sucrose and isopycnic PercollR centrifugation. These fractions were tested for mfVSG phospholipase activity using Trypanosoma brucei mfVSG labeled with 3H-myristic acid as substrate. The highest enzyme-specific activity was associated with the flagella and evidence is presented to suggest that it is localized in the flagellar pocket. Some activity was also associated with the Golgi complex. These results suggest that the mfVSG phospholipase is localized primarily in the membrane of the flagella pocket and possibly other membrane organelles derived from and associated with this structure, and may be part of the VSG-membrane recycling system in African trypanosomes. The activity of mfVSG phospholipase amongst various trypanosome species was determined. We show that, in contrast to the bloodstream forms of Trypanosoma brucei, cultured procyclic Trypanosoma brucei and bloodstream Trypanosoma vivax had little or no mfVSG phospholipase activity. The activity found in bloodstream forms of Trypanosoma congolense was intermediate between Trypanosoma vivax and Trypanosoma brucei.